Structural-parametric synthesis of the digital robust flight control system - Тунік А.A.; Галагуз T.А. (Proceedings of National Aviation University (archive), 2004)
The paper is devoted to the synthesis of the digital controller for a system with stochastic disturbances and incomplete measurements of the state vector. Then parametric robust optimization of obtained system is conducted to achieve stabilization and acceptable performance for nominal and parametrically disturbed plants using the same controller. Research is performed at the example of the small Unmanned Aerial Vehicle flight control system.